1993
DOI: 10.7863/jum.1993.12.10.577
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of ovarian volume and cysts in female isosexual precocious puberty

Abstract: The real-time pelvic sonograms of 32 girls under 8 years old with true isosexual precocity (23 cases), pseudosexual precocity (four cases), premature adrenarche (four cases), and an undetermined problem (one case) were evaluated retrospectively for ovarian volume and presence and size of cysts. Sonographic findings were compared to those of 181 age-matched controls to determine the best sonographic indicator of precocious puberty. Ovarian volume was 4.6 cm3 in girls with true isosexual precocity, 4.1 cm3 in gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 1 publication
2
27
0
Order By: Relevance
“…In our study, a homogeneous, solid echopattern was present in a higher proportion in younger ages, whereas macrocystic ovaries appeared after the age of 8 years and were seen with a higher frequency after the age of 10, even in prepubertal subjects ( Figure 5). This presence of ovarian follicles in prepubertal subjects has also been described by others 5,7,8,12,13,20,22 and has been confirmed by postmortem studies that have shown that ovaries are active throughout child- hood with an increasing number and size of follicles. 23 With regard to Tanner staging, our results show, surprisingly, that there is no statistically significant difference in uterine and ovarian size between prepubertal and pubertal subjects aged 10-12 years ( Figure 6).…”
Section: Discussionsupporting
confidence: 51%
“…In our study, a homogeneous, solid echopattern was present in a higher proportion in younger ages, whereas macrocystic ovaries appeared after the age of 8 years and were seen with a higher frequency after the age of 10, even in prepubertal subjects ( Figure 5). This presence of ovarian follicles in prepubertal subjects has also been described by others 5,7,8,12,13,20,22 and has been confirmed by postmortem studies that have shown that ovaries are active throughout child- hood with an increasing number and size of follicles. 23 With regard to Tanner staging, our results show, surprisingly, that there is no statistically significant difference in uterine and ovarian size between prepubertal and pubertal subjects aged 10-12 years ( Figure 6).…”
Section: Discussionsupporting
confidence: 51%
“…The presence of cysts alone, isolated from ovarian volume and other morphologic criteria, is not a reliable indicator of stimulation. 5 The suppressed ovaries may contain more than one 5 mm cyst in addition to minute hypoechoic follicles (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…8 The regression of all sonographic parameters after 1 year of therapy has been documented. 5 Our series represents a longitudinal study in which the patients were evaluated at uni· form time intervals with sonographic, laboratory and clinical correlates obtained on the same day. The time course of the hormonal-gonadal interaction is an important factor to keep in mind when evaluating these patients.…”
Section: Discussionmentioning
confidence: 99%
“…This may also allow differentiation between true isosexual precocity when the enlargement of the ovaries is bilateral, and pseudosexual precocity in which there is unilateral ovarian enlargement (King et al, 1993). Moreover, measurement of ovarian volume is the most sensitive index with which to assess the efficiency of GnRH analogue treatment of these cases (Ambrosino et al, 1994;Jensen et al, 1998).…”
Section: Abnormalities Of Adolescencementioning
confidence: 99%
“…Precocious puberty and growth disorders (Stanhope et al, 1985) Idiopathic precocious puberty, hypogonadotrophic hypogonadism (King et al, 1993) Isosexual precocity, pseudosexual precocity, premature adrenache (Bridges et al, 1993) GH insufficiency, skeletal dysplasia, tall stature (Ambrosino et al, 1994) Isosexual precocity (Griffin et al, 1995b) Precocious puberty, premature thelarche (Ciotti et al, 1995) Precocious puberty (Haber et al, 1995) Premature thelarche, central precocious puberty (Bridges et al, 1995) Untreated central precocious puberty, central precocious puberty treated with GnRHa, premature thelarche, premature adrenarche (Jensen et al, 1998) Idiopathic central precocious puberty Menstrual disorders (Venturoli et al, 1995) Persistent menstrual irregularity (Herter et al, 1996) Menstrual irregularity Eating disorders (Lai et al, 1994) Anorexia nervosa (Sobanski et al, (1997) Anorexia nervosa (Andolf et al, 1997) Anorexia nervosa, bulimia GH = growth hormone; GnRHa = gonadotrophin hormone releasing hormone agonoist. Zaidi et al (1995) measured stromal peak systolic blood flow velocity (V max ) on day 2-3 of cycles of PCOS patients and normal controls (Zaidi et al, 1995).…”
Section: Ovarian Volume and Doppler Blood Flowmentioning
confidence: 99%